2018
DOI: 10.3390/genes9090453
|View full text |Cite
|
Sign up to set email alerts
|

Molecular Characterization of Near Full-Length Genomes of Hepatitis B Virus Isolated from Predominantly HIV Infected Individuals in Botswana

Abstract: The World Health Organization plans to eliminate hepatitis B and C Infections by 2030. Therefore, there is a need to study and understand hepatitis B virus (HBV) epidemiology and viral evolution further, including evaluating occult (HBsAg-negative) HBV infection (OBI), given that such infections are frequently undiagnosed and rarely treated. We aimed to molecularly characterize HBV genomes from 108 individuals co-infected with human immunodeficiency virus (HIV) and chronic hepatitis B (CHB) or OBI identified f… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

4
32
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 19 publications
(36 citation statements)
references
References 121 publications
(182 reference statements)
4
32
0
Order By: Relevance
“…With the aid of a phylogenetic tree, we were able to show that HBV in our participants belongs to genotype A and mostly subgenotype A1. Our observation is in accordance with the previous studies that reported genotype A as the most prevalent HBV genotype in Southern Africa . Using an amino acid alignment, we observed protein sequence differences between sequences from participants and the reference genotype A sequence.…”
Section: Discussionsupporting
confidence: 92%
See 1 more Smart Citation
“…With the aid of a phylogenetic tree, we were able to show that HBV in our participants belongs to genotype A and mostly subgenotype A1. Our observation is in accordance with the previous studies that reported genotype A as the most prevalent HBV genotype in Southern Africa . Using an amino acid alignment, we observed protein sequence differences between sequences from participants and the reference genotype A sequence.…”
Section: Discussionsupporting
confidence: 92%
“…Our observation is in accordance with the previous studies that reported genotype A as the most prevalent HBV genotype in Southern Africa. 40,41 Using an amino acid alignment, we observed protein sequence differences between sequences from participants and the reference genotype A the MHR observed in two participants was previously reported. 42 The commonly described sG145R mutation associated with OBI was not found in our study.…”
Section: Discussionmentioning
confidence: 58%
“…The algorithm developed above was used to determine the impact of 43 OBI-associated mutations from Botswana, which have been described in detail elsewhere [ 73 ]. Several of these mutations have been characterized in vitro previously, while others have been reported but not functionally characterized in vitro.…”
Section: Resultsmentioning
confidence: 99%
“…The sequencing of the HBV genomes was reported in detail elsewhere [ 73 ]. Briefly, nearly whole HBV genome was successfully sequenced from 50 of 109 participants (37 CHB and 72 OBI positive) using big dye sequencing chemistry.…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation